Technology-Information Processing Fit and the Performance of R&D Project Groups: A Test of Contingency Theory - Keller, Robert T. (Academy of Management Journal, 1994)
A study of 98 R&D project groups using a longitudinal design found support for the contingency theory hypothesis that the fit between a task technology's nonroutineness and information-processing needs will predict project performance. The hypothesis was supported for concurrent and one-year-later management ratings of project quality, using absolute difference scores as a measure of fit. The fit between a technology's unanalyzability and information processing, however, was not a predictor of project performance. Implications for contingency design theory and the management of R&D project groups are discussed.